Sfp-type PPTase inactivation promotes bacterial biofilm formation and ability to enhance wheat drought tolerance - Timmusk, Salme; Kim, Seong-Bin; Nevo, Eviatar; Abd El Daim, Islam; Ek, Bo; Bergquist, Jonas; Behers, Lawrence (Frontiers in Microbiology, 2015)
Paenibacillus polymyxa is a common soil bacterium with broad range of practical applications. An important group of secondary metabolites in P. polymyxa are nonribosomal peptide and polyketide derived metabolites (NRP/PK). Modular nonribosomal peptide synthetases catalyse main steps in the biosynthesis of the complex secondary metabolites. Here we report on the inactivation of an A26 sfp-type phosphopantetheinyl transferase. The inactivation of the gene resulted in loss of NRP/PK production. In contrast to the former Bacillus spp. model the mutant strain compared to wild type showed greatly enhanced biofilm formation ability. Its biofilm promotion is directly mediated by NRP/PK, as exogenous addition of the wild type metabolite extracts restores its biofilm formation level. Wheat inoculation with bacteria that had lost their sfp-type PPTase gene resulted in two times higher plant survival and about three times increased biomass under severe drought stress compared to wild type.